Song and the song control pathway in the brain can develop independently of exposure to song in the sedge warbler. - Leitner, Stefan (2002)
Previous studies have shown that female sedge warblers choose to mate with males that have more complex songs, and sexual selection has driven the evolution of both song complexity and the size of the major song control area (HVc) in the brain. In songbirds, learning from conspecifics plays a major role in song development and this study investigates the effects of isolation and exposure to song on song structure and the underlying song control system. Sibling pairs of hand-reared nestling sedge warblers were reared to sexual maturity under two conditions. Siblings in one group were reared individually in acoustic isolation in separate soundproof chambers. In the other group, siblings were reared together in an aviary with playback of recorded songs. The following spring, analysis of songs revealed that siblings reared in acoustic isolation produced normal song structures, including larger syllable repertoires than those exposed to song. We found no significant differences in the volumes of HVc, nucleus robustus archistnatalis, the lateral portion of the magnocellular nucleus and the density of dendritic spines between the two groups. Males exceeded females in all these measures, and also had a larger telencephalon. Our experiments show that complex song, sexual dimorphism in brain structure, and the size of song nuclei can all develop independently of exposure to song. These findings have important implications for how sexual selection can operate upon a complex male trait such as song and how it may also shape the more general evolution of brain structure in songbirds.